Matched retrospective analysis of three different fixation devices for chevron osteotomy. (June 2021) - Wendelstein, Jascha; Holzbauer, Matthias; Neubauer, Markus; Steiner, Gernot; Gruber, Florian; Schneider, Wolfgang
Highlights: Magnesium screw, metal screw, and K-wire fixation provided satisfying results. All devices showed improvement regarding preoperative and postoperative joint angles. Magnesium screw fixation shows high postoperative satisfaction rates. Magnesium screw implantation implies a steeper learning curve. Abstract: Chevron osteotomy with consecutive fixation is a commonly performed operative treatment option for hallux valgus deformities. The present retrospective study aims to compare the clinical and radiological outcome of novel bioabsorbable magnesium screw fixation with metal screw and Kirschner wire fixation. Eighteen matched triplets were assembled according to the following criteria: female gender, age difference less than 5 years, date of operation within 4 months, difference in preoperative intermetatarsal angle less than 5°, and equal experience of the first and second surgeon. These patients, between 18 and 85 years of age and with a minimum follow-up period of 12 months, were invited to a follow-up examination, of which only 16 matched triplets of patients entirely kept the appointment. Thus, 48 feet of 44 patients were clinically evaluated using the American Orthopaedic Foot & Ankle Society scale, Foot Function Index, University of California and Los Angeles Activity Score, as well as a visual analogue scale for pain, satisfaction, cosmetic results, and functional impairment. Radiographical assessment included measuring intermetatarsal angle and first metatarsophalangeal angles. All occurring complications and revision surgeries were noted. Significant differences were observed for postoperative intermetatarsal angle between magnesium screw and pin fixation (p = 0.009). Moreover, patients receiving magnesium screw were significantly more prone to undergo the same procedure again (p = 0.03). In conclusion, if the advantages of bioabsorbable magnesium screws outweigh the drawbacks of increased costs and a higher surgical demand, this implant might serve as possible chevron osteotomy fixation method. Compression screws and Kirschner wires also show comparable satisfactory outcomes. Level of evidence: III retrospective comparative study